Adsorptive scavenging of cationic dyes from aquatic phase by H3PO4 activated Indian jujube (Ziziphus mauritiana) seeds based activated carbon: Isotherm, kinetics, and thermodynamic study - Khan, Tabrez Alam; Nouman, Md; Dua, Divya; Khan, Suhail Ayoub; Alharthi, Salman S. (Journal of Saudi Chemical Society, 2022)
In the present work, a cost-effective Indian jujube seeds derived activated carbon (IJSAC) prepared via o-phosphoric acid chemical activation, is studied for the sequestration of acriflavine (AF) and Victoria blue B (VB) from the aquatic environment. The activated carbon is characterized by Fourier transform infrared spectroscopy, N2-adsorption/desorption isotherm, scanning electron microscopy techniques and point of zero-charge measurement. The specific surface area (SBET) of 571 m2/g with a pore radius of 22.45 Å specifies mesoporous nature of the IJSAC. The implication of operational conditions on the adsorption of both dyes onto IJSAC assessed by batch methodology, establish the optimal conditions as dosage (1.5 and 2.5 g/L), contact time (60 min), pH (8 and 10), and initial concentration (130 and 140 mg/L) for AF and VB uptake, respectively. The Freundlich adsorption isotherm model (R2 = 0.99) appropriates the equilibrium data suggesting multilayer adsorption onto heterogeneous surface sites, while pseudo-second order (R2 = 0.95–0.99) is the best fit kinetic model. The liquid film and intraparticle diffusion modelling demonstrate that the adsorption process of these dyes is governed by both the steps. Maximum Langmuir adsorption capacity is 113.6 mg/g for acriflavine and 92.78 mg/g for Victoria blue B. Thermodynamic studies indicate endothermic and spontaneous adsorption of dyes. The adsorption mechanism for the uptake of AF and VB by IJSAC most probably involves hydrogen bonding, electrostatic and π-π interactions. Based on its high adsorption capacity, relatively faster kinetics, and reusability, IJSAC can be perceived as a proficient and effective adsorbent for cationic dyes removal from the liquid waste.